A Novel Framework for Big Data Analytics in Business Intelligence - Bhat, Prashant; Hegde, Prajna; Malaganve, Pradnya (International Journal of Computer Sciences and Engineering, 2018)
In recent years, due to new technologies databases are growing rapidly. This has resulted in evolution of term “Big Data”. Big Data is nothing but huge data sets that can be processed and analysed to get useful information. Big Data Analytics is the process of inspecting large datasets, extracting information from it. These meaningful information obtained from large data sets can be utilized in business. Big Data Analytics helps business to take innovative, better decisions so as to improve business output. Big Data is large in size, grows very quickly hence impossible for traditional systems to process it. In this paper we review the importance of Big Data, Big Data Analytics and we propose an approach for using uncovered patterns, information of Big Data Analytics in Business Intelligence. Also an attempt is made in listing challenges in Big Data Analytics.